Clinical and Microbiologic Efficacy of a Water Filter Program in a Rural Honduran Community. (7th April 2014) - Arquiette, Jaclyn; Stevens, Michael P.; Rabb, Jean M.; Sanogo, Kakotan; Mason, Patrick; Bearman, Gonzalo M. L.
Abstract : Water purification in the rural Honduras is a focus of the nonprofit organization Honduras Outreach Medical Brigade Relief Effort (HOMBRE). We assessed water filter use and tested filter microbiologic and clinical efficacy. A 22-item questionnaire assessed water sources, obtainment/storage, purification, and incidence of gastrointestinal disease. Samples from home clay-based filters in La Hicaca were obtained and paired with surveys from the same home. We counted bacterial colonies of four bacterial classifications from each sample. Sixty-five surveys were completed. Forty-five (69%) individuals used a filter. Fifteen respondents reported diarrhea in their home in the last 30 days; this incidence was higher in homes not using a filter. Thirty-three paired water samples and surveys were available. Twenty-eight samples (85%) demonstrated bacterial growth. A control sample was obtained from the local river, the principal water source; number and bacterial colony types were innumerable within 24 hours. Access to clean water, the use of filters, and other treatment methods differed within a geographically proximal region. Although the majority of the water samples failed to achieve bacterial eradication, water filters may sufficiently reduce bacterial coliform counts to levels below infectious inoculation. Clay water filters may be sustainable water treatment measures in resource poor settings.